Examining The Impact of Short-Form Video Content on Brand Perception for Higher Education Institutions Across Different Social Media Platforms: A Systematic Literature Review - Aswin Alfa Rabyn; Nabil Muttaqin; Dwi Soca Baskara; Dio Lingga Purwodani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study investigates the profound influence of short-form video content, specifically clips under 60 seconds, on shaping brand perception and fostering engagement within the higher education sector. It encompasses a comprehensive systematic review of 22 studies, drawing insights from universities across nine diverse countries. The research meticulously analyzes platform-specific strategies employed on major social media channels, utilizing a range of methodologies including observational, qualitative, and mixed-methods designs. Key findings reveal distinct performance metrics across platforms: TikTok demonstrates exceptionally high engagement rates at 4.38%, while YouTube boasts impressive video completion rates, averaging 80%. A critical insight emphasizes the necessity for universities to adapt their content to the unique norms and audience behaviors of each platform to maximize impact. This study significantly contributes to the field by providing a robust framework for evaluating the effectiveness of short-form video in educational marketing. Furthermore, it advances theoretical understanding regarding platform-specific strategies in the dynamic landscape of higher education branding.